THE DEVELOPMENT OF EDUCATIONAL THEORIES AND ITS IMPLEMENTATION ON NATIONAL EDUCATION SYSTEM IN INDONESIA: PERKEMBANGAN TEORI PENDIDIKAN DAN IMPLEMENTASINYA DALAM SISTEM PENDIDIKAN DI INDONESIA - Desi Rochmawati; Sunardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Theories related to learning and education has developed since Greece and Roman era. The philosophers have already convinced the society with their thoughts of learning even though there are still some polemics and pro contra among experts. Their concepts have brought some changes dan influences to human education including an educational system in Indonesia. This article aimed at elaborating the development of educational theories and the implementation of those theories in educational system in Indonesia to get better understanding of the theories. In writing this article, a historical library research method was used to get data and information related to the topic. Relevant journals and books were used as the references to support the writing of this article. The result shows that concepts in education were used as references to build proper form of curriculum in Indonesia. It has important roles in developing national education which finally Indonesia has ten times revised the curriculum to get better educational system and work in line with the development era. Keywords: curriculum; educational concepts; national education; theories of learning